Circulation, writing, and rhetoric - Gries, Laurie E.; Brooke, Collin Gifford (Utah State University Press, 2018)
"It has been understood that writers quote, imitate, forward, borrow, dispute, engage with, and transform texts written by others. Contributors identify circulation as a threshold concept of Western literacy theory and explore five key themes concerning circulation: public rhetorics, feminism, new materialism, theories of delivery, and technologies"--Provided by publisher.
Keywords: Rhetoric -- Social aspects.; Communication in learning and scholarship.; Rhétorique -- Aspect social.; Communication savante.; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing.; LANGUAGE ARTS & DISCIPLINES -- Rhetoric.; REFERENCE -- Writing Skills.; Communication in learning and scholarship; Rhetoric -- Social aspects